Pengaruh Flash Sale, Electronic Word Of Mouth, dan Hedonic Shopping Motivation Terhadap Impulse Buying pada Tokopedia: Studi pada Pengguna Tokopedia di Surabaya - Carissa Ruth Malinda; Siti Ning Farida (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research was conducted with the aim of analyzing and knowing the effect of flash sales, electronic word of mouth, and hedonic shopping motivation on impulse buying on Tokopedia users in Surabaya. This study uses associative quantitative research. The measurement scale used in this study is a Likert scale (method of summated ratings). The sample in this study used the Cochran formula with the results totaling 96.04. To get more representative results in this study, the authors drew 100 respondents using non-probability sampling techniques. In addition, a purposive sampling approach was applied in the sampling strategy in this study. The considerations or criteria in determining the sample in this study, namely: Surabaya domiciled Tokopedia users; Minimum age 17 years and Have made purchases through Tokopedia more than 2 times. The types of data used in the study, namely primary and secondary data. The questionnaire data that has been obtained will be measured using the IBM SPSS 25 application by conducting validity tests, reliability tests, classical assumption tests, multiple linear regression tests, and hypothesis testing. The results of this study state that simultaneously flash sales, electronic word of mouth, and hedonic shopping motivation have a positive and significant effect on impulse buying. Furthermore, partially the flash sale variable has a positive and significant effect on the impulse buying variable, partially the electronic word of mouth variable has a positive and significant effect on impulse buying, and partially hedonic shopping motivation has a positive and significant effect on impulse buying on Tokopedia users in Surabaya.